A comparison of numerical investigations on the flow and heat transfer characteristics in the rotor-stator cavity. (5th November 2019) - Liao, Gaoliang; Liu, Lijun; Zhang, Feng; Jiaqiang, E; Chen, Jingwei
Highlights: The heat transfer characteristics in the rotor-stator disc cavity were investigated. The distributions of pressure, radial velocity and temperature were discussed. The distribution of heat transfer coefficient was also presented. The predicted parameters showed a good agreement with the experimental data. Abstract: This paper presents an application of conjugate CFD and fully coupled FE/CFD to investigate the flow and heat transfer characteristics in the rotor-stator disc cavity. The results are compared with that predicted by the steady-state flow analysis and experimental data. The commercial solvers of System Coupling module integrated in ANSYS Workbench and CFX 15.0 coupled with standard k - ε turbulence model are adopted. The distributions of pressure, radial velocity, temperature and heat transfer coefficient in the rotor-stator disc cavity are discussed in detail. The results obtained in this study indicate that in the case of low secondary air flow, the predicted pressure from fully coupled FE/CFD shows a good agreement with the experimental data while the other two numerical methods provide a slight deviation from the experiment. With large secondary air flow, the pressure distributions predicted numerically are well matched with the measured values. The steady-state flow and conjugate CFD could predict well the thermal boundary near the rotor surface while the fully coupled FE/CFD overpredicts the thickness of thermal boundary. The fully coupled FE/CFD predicts well the heat transfer coefficients with the experimental data.